HIV viral load suppression among people with mental disorders at two urban HIV clinics in Uganda: a parallel convergent mixed methods study using the social ecological model - Regina Ndagire; Rachel Nante Wangi; Kevin Ouma Ojiambo; Joanita Nangendo; Juliet Nakku; Herbert Muyinda; Fred C. Semitala (AIDS Research and Therapy, 2023)
Abstract Background Uganda adopted and implemented the Universal Test and Treat (UTT) guidelines in 2017, which require HIV-infected persons to be initiated on antiretroviral therapy (ART) at any CD4 + cell count, and to be routinely monitored for viral load to assess response to ART. However, there is paucity of data on viral load suppression (VLS) among people living with HIV (PLHIV) with mental disorders. We conducted a parallel convergent mixed methods study to determine HIV VLS among people with a mental disorder and explored the socio-cultural determinants of VLS at Butabika hospital and Mulago (ISS) HIV Clinics in Uganda. Methods We conducted a retrospective medical records review; seven key informant interviews (KII) among purposively selected healthcare providers and 12 in-depth interviews (IDI) among clinically stable PLHIV with a mental disorder. Data was collected on demographics, mental disorder, ART, viral load status, social support, stigma, and disclosure of HIV status. Quantitative data was analysed using descriptive statistics and modified Poisson regression, while Inductive thematic analysis was used for the qualitative data. Results Of the 240 PLHIV with a mental disorder who were enrolled, 161 (67.1%) were female with mean age 38.9 (± 11.2) years. Overall, 88.8% (95% Cl: 84.0 – 92.2%) achieved VLS. Age (aPR = 1.00, 95%Cl = 1.00–1.00), male gender (aPR = 0.90, 95%Cl = 0.82–0.98), divorced (aPR = 0.88, 95%Cl = 0.82–0.94), widowed (aPR = 0.84, 95%Cl = 0.83–0.86), baseline CD4 count < 200 (aPR = 0.89, 95%Cl = 0.85–0.94), psychotic mental disorders (aPR = 1.11; 95%CI = 1.08–1.13) and fair (85–94%) ART adherence level (aPR = 0.69, 95%Cl = 0.55–0.87) and TDF/3TC/DTG (aPR = 0.92; 95%CI = 0.91–0.94) were associated with HIV VLS. Social support from family members, knowledge of impact of negative thoughts on VLS, fear of breaking up with partners and compassionate healthcare providers positively influenced VLS. Stigma and discrimination from the community, self-perceived stigma hindering social relations, socio-economic challenges and psychiatric drug stock-outs negatively affected VLS. Conclusion and recommendations HIV VLS among PLHIV with mental disorders at institutions that provide integrated HIV and mental health care is still below the UNAIDS 95% target. Health promotion messaging focusing on benefits of VLS and countering stigma to create a safe environment; and active involvement of family members in care could improve HIV treatment outcomes for PLHIV with mental disorders.